Portraits of Graduates in Becoming Multilingual and Multicultural Citizens in the Context of Internationalization - Abduh, Amirullah; Jayadi, Karta; Dunakhir, Samirah (International Journal of Language Education, 2021)
The purpose of this paper was to investigate the portraits of graduates who have learned English as a foreign language on one hand, while maintaining Indonesian and local languages on the other. This study draws on poststructuralist notions of identity and language learning and uses a portraiture lens emphasising contexts and voice. This paper draws on data from semi-structured interviews and focus group interviews of five key participants relating their contextual backgrounds and their efforts to be bilinguals. Learning an additional language requires systemic and multifaceted overarching approaches over relatively long periods of time rather than a single strategy within a short period. These efforts have contributed them to beome multilingual and multicultural individuals.Â  Empirical evidence shows that situational factors such as language exposure and motivation play dominant roles to assists learners to be bilingual and biliterate individuals. The situational factors link closely to the exposure in terms of quantity and quality of experiences to the target language.Â  They are, nevertheless, valuable as portraits of learners.